#MissingData: A methodological inquiry of the hashtag to collect data from Twitter - D’heer, Evelien; Verdergem, Pieter; De Grove, Frederik (AoIR Selected Papers of Internet Research, 2016)
In this paper, we assess the Twitter hashtag from a methodological perspective. Compared to conventional methods in social science research (such as surveys and in-depth interviews), social media as a method is far from being fully understood. We evaluate a popular sampling procedure for Twitter studies, i.e. the hashtag approach. Hashtags are valuable to study the emergence and evolution of Twitter debates around particular topics. However, not all relevant tweets are captured. In particular, we refer to the exclusion of @replies prompted by hashtagged tweets.This paper empirically examines the impact of hashtag sampling on conversation networks.